Clinical utility of 99mTc-ubiquicidin (29–41) as an adjunct to bone scan in differentiating infected versus noninfected loosening of prosthesis before revision surgery. Issue 4 (April 2017) - Shinto, Ajit S.; Mukherjee, Archana; Karuppusamy, Kamalaeshwaran Koramadai; Joseph, Jephy; Bhatt, Jyotsna; Korde, Aruna; Upadhya, Indira; Arjun, Chanda; Samuel, Grace; Dash, Ashutosh
Abstract : Purpose: The aim of this study was to evaluate the utility of 99m Tc-ubiquicidin ( 99m Tc-UBI) (29–41) as an adjunct to an methylene diphosphonate (MDP) bone scan in differentiating septic versus aseptic loosening in patients with painful prosthesis posted for revision surgery. Patients and methods: A two-vial cold kit of UBI (29–41) was prepared and utilized for the preparation of patient dose of 99m Tc-UBI (29–41). Twenty two patients with painful hip or knee prosthesis and scheduled for revision surgery were included in the study. Overall, 370–555 MBq of 99m Tc-UBI (29–41) was injected intravenously in all the patients. A blood pool image at 20 min after injection was followed by spot views of the suspected region of infection (target) and a corresponding normal area (nontarget) at 60 min. All patients underwent a routine 99m Tc-MDP three-phase whole-body bone scan, followed by single-photon emission computed tomography/computed tomography of the prosthesis within a week of the 99m Tc-UBI (29–41) study. For 99m Tc-UBI scans, a visual score (0–3) was used to categorize studies as positive or negative, with scores of 0 (minimal or no uptake; less than soft tissue or contralateral extremity) and 1 (mild; equivalent to soft tissue or contralateral extremity) being considered negative and scores of 2 (moderate; uptake greater than soft tissue or contralateral extremity, but less than the liver) or 3 (intense; uptake greater than soft tissue or contralateral extremity and equivalent to the liver) being considered positive. The final correlation was on the basis of bacterial culture as the major criterion and the results of clinical tests, radiography, fluorine-18-fluorodeoxyglucose PET-CT, and three-phase bone scanning as the minor criteria. Results: In all, 22 studies were carried out with 99m Tc-UBI (29–41). Of these, 16 scans were considered positive and six were negative for infection foci. All negative scans were subsequently confirmed to be true negative. Adverse reactions were not observed during image acquisition and within 5 days after the study. The overall sensitivity, specificity, and positive and negative predictive values were 100, 85.7, 93.75, and 100%, respectively. A combination of an MDP bone scan and UBI scans was considered to yield maximum confidence toward reporting for the presence of infection. Conclusion: Patient dose of 99m Tc-UBI (29–41) was prepared successfully and a simple quality control method to check radiolabeling yield was used at the hospital radiopharmacy. 99m Tc-UBI (29–41) showed promise in localizing foci of infection, with optimal visualization at 20–60 min, for the evaluation of prosthesis loosening.